Comparative Assessment of Soil-Borne Potato Nematodes Across Agro-Ecological Zones and their Implications for Crop Management - Kumari, Supriya; Kumar, Vijay (American Journal of Biology and Natural Sciences, 2025)
Potato (Solanum tuberosum L.) is one of the major cash and food crops of Bihar and plays a significant role in the economy of Vaishali district. However, potato production in the region is frequently hampered by soil-borne plant-parasitic nematodes that attack roots, reduce nutrient uptake, and cause severe yield losses. Among these, Meloidogyne spp. (root-knot), Globodera spp. (cyst), and Pratylenchus spp. (lesion) are of primary concern. Despite their importance, there is limited comparative information on nematode diversity, density, and distribution across the district’s varying agro-ecological conditions. This study therefore proposes a comparative assessment of soil-borne potato nematodes in Mahua and Gandak agro-ecological zones of Vaishali, with a focus on their population dynamics, environmental interactions, and implications for crop management. Field surveys and systematic sampling will be conducted during the active potato-growing season. Soil and root samples will be collected from selected villages of both agro-ecological zones, covering different soil types, cropping histories, and irrigation patterns. Nematodes will be extracted using Cobb’s decanting and sieving technique and identified to the genus or species level through morphological and molecular methods. Soil parameters such as pH, texture, organic carbon, and nutrient content will be analyzed. The data will be statistically examined using correlation and multivariate analyses (PCA, CCA) to determine relationships between nematode populations and soil- environmental factors. This research holds scientific and practical significance, as it will generate baseline data on nematode diversity and soil relationships in Vaishali district an area with high agricultural potential but limited nematological studies. By linking nematode ecology with soil and crop management, the findings will guide farmers and agricultural planners toward sustainable pest management practices, improve productivity, and preserve soil health. Ultimately, this comparative assessment will strengthen the foundation for long-term nematode monitoring and management programs in Bihar’s potato-growing ecosystems.